2009
DOI: 10.1136/emj.2008.068122
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection in a case of Turner's syndrome

Abstract: A case report is presented of an aortic dissection in a patient with Turner's syndrome that went undiagnosed. A thorough discussion of this fatal condition in this group of patients is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…An influential early study suggested that aortic disease in Turner syndrome was similar to that in Marfan syndrome, characterized by ‘cystic medial degeneration’, which is the common pathophysiology for aortic root dilation [1113]. However, there is no evidence to suggest that patients with Turner syndrome experience progressive dilatation of the aorta over time, in the absence of predisposing risk factors, as seen in Marfan syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An influential early study suggested that aortic disease in Turner syndrome was similar to that in Marfan syndrome, characterized by ‘cystic medial degeneration’, which is the common pathophysiology for aortic root dilation [1113]. However, there is no evidence to suggest that patients with Turner syndrome experience progressive dilatation of the aorta over time, in the absence of predisposing risk factors, as seen in Marfan syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…To gain a better understanding of the natural history of Turner’s syndrome, the International Turner Syndrome Aortic Dissection Registry has been established. It remains unclear whether girls with Turner syndrome should undergo surveillance, with routine electrocardiogram and blood pressure testing [13]. Some reports recommended that Turner syndrome with known congenial heart disease should undergo comprehensive cardiac magnetic resonance imaging evaluation, close cardiologic follow-up, control of blood pressure, and a trial of angiotensin antagonist versus beta-blocker [6,14].…”
Section: Discussionmentioning
confidence: 99%